Associação entre amamentação e alterações da sobremordida na dentadura decídua - Romero, Camila Campos (2007)
The aim of this study was to investigate the association between exclusive breast-feeding duration and alterations in overbite, specifically anterior open bite, on primary dentition. The sample consisted of 1377 children of both sexes, aged 3 to 6 years, enrolled at 11 public pre-schools run by the municipality in the eastern region of São Paulo – SP. The methods and duration of infant feeding, as well as the history of non-nutritive sucking habits, were researched by means of a questionnaire applied to the parents/guardians. Clinical examinations were performed by 3 calibrated dentists (: 0.89-1.00 and Rs > 0.90), who classified overbite into 5 categories: normal, null, anterior open bite, moderately increased, and severely increased. Children were grouped according to the duration of exclusive breast-feeding and age of non-nutritive sucking habits persistence: G1 – non-breast-fed, G2 – exclusive breast-feeding at maximum to 5 months of age, G3 – exclusive breast-feeding discontinued between 6 and 12 months of age, and G4 – exclusive breast-feeding for longer than 12 months of age; Control – without history of pacifier and/or digit sucking habits, Up to 2 years – habit that persisted up to 2 years of age, From 3 to 4 years – habit discontinued between the ages of 3 and 4 years, From 5 to 6 years – habit discontinued between the ages of 5 and 6 years. Descriptive statistical analysis was used, with distribution of the frequencies relative to the data on infant feeding, non-nutritive sucking habits and overbite characteristics. The study groups were compared for the prevalence of anterior open bite by the Chi-Square test (p < 0.05), with odds ratio (or) calculation. Considering the groups G1, G2, and G3, mean exclusive breast-feeding durations for children with and without anterior open bite were compared by the Student’s-t test (α = 0.05). Prevalence values of anterior open bite were gradually lower for G2 (26.1%), G3 (22.1%), and G4 (6.2%) in comparison with G1 (31.9%). In the total sample and in the Control group, non-breast-fed children would have 7.1 (p < 0.001) and 9.3 (p = 0.009) more chance of presenting anterior open bite than those that were exclusively breast-fed beyond 12 months of age, respectively. The children with habits that lasted from 3 to 4 years and from 5 to 6 years of age would have 38.54 (p < 0.001) and 86.95 (p < 0.001) more chance of presenting anterior open bite, respectively, when compared with the Control group. There was significant difference in the mean exclusive breast-feeding duration between children with (3.5 ± 0.32 months) and without (3.9 ± 0.18 months) anterior open bite (t = 1.99, p = 0.047). It was concluded that the chances of anterior open bite occurring were significantly greater for non-breast-fed children in comparison with those that were exclusively breast-fed for periods longer than 12 months of age, evidencing the beneficial influence of breast-feeding on overbite.